PENGARUH HARGA, KUALITAS PRODUK, DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN KOPI LOKAL : Studi Kasus Pada Tarzzan Coffee Roastery (Jurnal Riset Akuntansi dan Bisnis Indonesia, 2023)
The purpose of this test is to examine: (1) does price affect purchasing decisions, (2) does product quality affect purchasing decisions, (3) does brand image affect purchasing decisions, (4) does price, product quality, and brand image influences the purchasing decision of local coffee products at Tarzzan Coffee Roastery. The sample in this test is a portion of Tarzzan Coffee Roastery visitors who usually enjoy processed local coffee, only 90 respondents using a purposive sampling technique. The instrument in this test is a questionnaire that has been tested for validity and reliability using Cronbach Alpha. The data analysis method used for testing is multiple linear regression by applying the SPSS version 25 data processing program. The test results are sourced from multiple linear tests indicating that: (1) there is no positive effect on price on purchasing decisions for local coffee at the Tarzzan Coffee Roastery, with the partial test results the t count value is 0.270 less than t table 1.98793 and the sig value is 0.788 greather than 0, 05 . (2) there is a positive influence on product quality on purchasing decisions for local coffee at the Tarzzan Coffee Roastery, with a t-value of 17.114 greather than 1.98793 and a sig value of 0.000 less than 0.05. (3) there is no positive influence on brand image on purchasing decisions for local coffee at the Tarzzan Coffee Roastery, with a t-count value of 1.775 less than 1.98793 and a sig value of 0.079 greather than 0.05. (4) there is a positive influence on price, product quality, and brand image together on purchasing decisions for local coffee at the Tarzzan Coffee Roastery, with an F count of 340.688 greather than F table of 2.711 and a sig value of 0.000 less than 0.05.
Keywords: Price; Product Quality; Brand Image; and Purchase Decision